Labeling and Selective Inactivation of Gram‐Positive Bacteria Employing Bimodal Photoprobes with Dual Readouts. Issue 15 (1st March 2016) - Galstyan, Anzhela; Block, Desiree; Niemann, Silke; Grüner, Malte C.; Abbruzzetti, Stefania; Oneto, Michele; Daniliuc, Constantin G.; Hermann, Sven; Viappiani, Cristiano; Schäfers, Michael; Löffler, Bettina; Strassert, Cristian A.; et al.
Abstract: Carbohydrate‐conjugated silicon(IV) phthalocyanines with bimodal photoactivity were developed as probes with both fluorescent labeling and photosensitizing capabilities, and the concomitant fluorescent labeling and photoinduced inactivation of Gram‐positive and Gram‐negative models was explored. The maltohexaose‐conjugated photoprobe provides a dual readout to distinguish between both groups of pathogens, as only the Gram‐positive species was inactivated, even though both appeared labeled with near‐infrared luminescence. Antibiotic resistance did not hinder the phototoxic effect, as even the methicillin‐resistant pathogen Staphylococcus aureus (MRSA) was completely photoinactivated. Time‐resolved confocal fluorescence microscopy analysis suggests that the photoprobe sticks onto the outer rim of the microorganisms, explaining the resistance of Gram‐negative species on the basis of their membrane constitution. The mannose‐conjugated photoprobe yields a different readout because it is able to label and to inactivate only the Gram‐positive strain. Abstract : Bimodal probes : A versatile toolbox is presented for the construction of two phototriggered bimodal probes with distinctive readouts for the discrimination of E. coli and S. aureus . Because of their intrinsic fluorescence, the probes are able to label pathogens with or without selectivity for the Gram‐positive bacteria on the basis of the attached carbohydrate (see figure).